2015
DOI: 10.1007/s00044-015-1402-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and antinociceptive properties of the lappaconitine salts

Abstract: A series of diterpene alkaloid derivatives (1-6) are prepared by reaction of the lappaconitine (0) with the corresponding organic or inorganic acid. The lappaconitine was isolated from the root of Aconitum sinomontanum Nakai in Gansu Province in China. The structures of all newly synthesized compounds were established by analytical and spectral data. In particular, the configurations of compounds 0-3 were determined by X-ray single-crystal diffraction. The analgesic potential has been investigated. Among the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Regents LA (pure > 97.7%) were purchased from Gansu Xinlan Pharmaceutical Co., Ltd. LS (pure > 98.2% ) was synthesized according to the methods of Sun et al [11].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regents LA (pure > 97.7%) were purchased from Gansu Xinlan Pharmaceutical Co., Ltd. LS (pure > 98.2% ) was synthesized according to the methods of Sun et al [11].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the combination of LA and the chemotherapeutic agent oxaliplatin could enhance oxaliplatin-induced apoptosis in A549 cells [10]. Compared with LA and LH, LA sulfate (LS) exhibited a greater solubility in water and pronounced analgesic activity, without inducing undesirable side effects [11]. More importantly, we have previously reported that LS exhibited distinct antitumor effects via antiproliferation and the induction of apoptosis [12,13].…”
Section: Introductionmentioning
confidence: 99%
“… 96 In addition, the analgesic activity of LA salts is also affected by the kinds of ions, for example it was reported that the analgesic effect of LA hydrochloride is worse than that of its hydrobromide, 97 while another study revealed that LA sulfate exhibited a more pronounced analgesic activity than other salt forms. 98 …”
Section: Bioactivitiesmentioning
confidence: 99%
“…Almost all of the C 20 -diterpenoid alkaloids contain oxygenated groups. However, in contrast to the C 19 -diterpenoid alkaloids, C 20 -DAs possess the following distinctive features [ 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 ]: Most of them do not contain a methoxy group in their structures as C 19 -DAs [ 108 ]; Some alkaloids contain an acetoxy group or benzoyloxy ester group, or both, and do not incl...…”
Section: Classification Of Diterpenoid Alkaloidsmentioning
confidence: 99%
“…Lappaconitine (C18-DAs) shows pain-relief properties. However, lappaconitine sulfate, obtained by the modification of lappaconitine, exerts a more noticeable analgesic action than lappaconitine, which is poorly soluble in water [ 139 , 140 ].…”
Section: Bio-activities Of Dasmentioning
confidence: 99%